Pengaruh Keterlibatan Orang Tua Dalam Dukungan Dan Pengembangan Bakat Olahraga Anak-Anak Di Usia Dini - Umi Fityatul Millah; Rivan Saghita Pratama (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This article examines the impact of parental involvement in supporting and developing children's sports talents in early childhood. The study explores various factors influencing the level of parental engagement, including social, economic, cultural aspects, and personal experiences. Through a comprehensive literature review, the article identifies that effective parental involvement can enhance children's motivation, skills, and sports performance, while inadequate involvement can have negative consequences. The article also highlights the importance of support strategies tailored to the specific needs of families and cultural contexts, as well as the role of programs that facilitate parental engagement. The findings provide insights for designing more effective interventions to support the development of children's sports talents.